Therapeutic plasma exchange in chronic dysimmune peripheral neuropathies: A 10‐year retrospective study. Issue 6 (1st March 2017) - Codron, Philippe; Cousin, Maud; Subra, Jean‐François; Pautot, Vivien; Letournel, Franck; Verny, Christophe; Cassereau, Julien
Abstract: Introduction: Therapeutic plasma exchange (TPE) can be proposed in the treatment of chronic dysimmune peripheral neuropathies (CDPN). Actual guidelines are however based on few studies, and indications and protocols still remain to be clarified. We conducted a 10‐year retrospective study in order to assess the effectiveness and tolerance of TPE in CDPN. Methods: All patients treated for CDPN with TPE from October 2006 to March 2016 in the university hospital of Angers were included. Patients were considered responders when they presented a clinical improvement substantial enough to continue the treatment. The Hughes functional grading score was also determined for each patient before and after TPE initiation. Results: Among the 206 patients who received TPE during the study period, 30 (14.6%) met the diagnostic criteria of CDPN. Four of the five paraprotein neuropathies (PPN) patients (80%) and 8 of the 11 chronic inflammatory demyelinating polyneuropathies (CIDP) patients (72.7%) were responders, with a significant improvement of the Hughes score for the latter ( P = 0.013). None of the three Lewis–Sumner and the two POEMS patients showed substantial improvement. Six of the nine anti‐MAG neuropathy patients (66.7%) responded to treatment, with a trend towards improvement of the Hughes score ( P = 0.072). Conclusion: TPE appears to be effective in CIDP and PPN, and ineffective in Lewis‐Sumner and POEMS syndromes. Interestingly, anti‐MAG neuropathy patients showed a good rate of response to TPE. Regarding these preliminary results, a randomized trial would be very worthwhile in this disease for which there is no evidence based treatment to date.